Toll like receptor 2 mediated exacerbation of sepsis associated acute kidney injury by renal congestion in mice - Itaru Nakamura; Minato Umehara; Aya Yagi-Tomita; Satomi Yamamoto; Shinji Sawai; Masashi Nakamura; Atsushi Minamida; Hiroko Yamauchi-Sawada; Yasuto Sunahara; Yayoi Matoba; Natsuko Okuno-Ozeki; Kunihiro Nakai; et al. (Scientific Reports)
Abstract Renal congestion is a key factor in renal dysfunction associated with heart failure. We previously reported that renal congestion worsened renal ischemia-reperfusion in a murine model. However, its impact on sepsis-associated acute kidney injury (SA-AKI), the leading cause of AKI, remains unclear. Therefore, we herein investigated the mechanisms by which renal congestion exacerbates SA-AKI, with a focus on Toll-like receptor (TLR) 2. After inducing sepsis with cecal ligation and puncture (CLP) in a unilateral renal congestion model, transient blood pressure reductions and persistent renal vein dilation were observed. A histological analysis showed increased fibrosis and its markers in congested kidneys post-CLP. Acute phase results revealed extensive tubular damage, macrophage infiltration, TLR2 up-regulation, and elevated high mobility group box 1 (HMGB1) levels. In TLR2-knockout mice, exacerbation of tissue fibrosis by renal congestion was attenuated after CLP. In vitro, oxidative stress and hypoxia up-regulated TLR2 expression. Collectively, these results suggest that renal congestion and sepsis synergistically worsened renal damage, likely through hypoxia and the oxidative stress-induced activation of the TLR2 pathway.